2009
DOI: 10.1038/ajg.2009.389
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Study Evaluating the Safety and Efficacy of a New, Reduced-Volume, Oral Sulfate Colon-Cleansing Preparation for Colonoscopy

Abstract: The new 960 -ml oral sulfate solution is effective for colonoscopy cleansing and has an acceptable safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
153
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(164 citation statements)
references
References 13 publications
8
153
2
1
Order By: Relevance
“…An oral sulfate solution has also been assessed as a bowel cleansing agent for colonoscopy [Di Palma et al 2009;Pelham et al 2010;Rex et al 2010Rex et al , 2014aRex et al , 2014b and may also be used as an effective booster agent for CCE.…”
Section: Introductionmentioning
confidence: 99%
“…An oral sulfate solution has also been assessed as a bowel cleansing agent for colonoscopy [Di Palma et al 2009;Pelham et al 2010;Rex et al 2010Rex et al , 2014aRex et al , 2014b and may also be used as an effective booster agent for CCE.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have demonstrated that split dosing not only to improves patient acceptability, but also cleans the colon better [8] . Of 13 prospective, randomized studies done previously, 12 showed superior cleansing when whole or part of the bowel preparation was given in the morning of the scheduled colonoscopy [9][10][11][12][13][14][15][16][17][18][19][20][21] . However colonoscopies are often scheduled in the afternoon, and split dosing may not leave a clean colon by afternoon.…”
Section: Introductionmentioning
confidence: 99%
“…report the results of a randomized, multicenter, industry-sponsored, endoscopist-blinded trial of a novel oral sulfate solution for pre-colonoscopic bowel preparation (6) . Study subjects were randomized to one of two therapeutic dosing strategies: same-day (PM before examination) vs. split-dose (PM / AM) preparation.…”
mentioning
confidence: 99%